Ambulatory Medication Change Workflows' Effect on Communication to Pharmacies - Pitts, Samantha I.; Thomas, Bridgette; Yang, Yushi; Chen, Allen R. (Applied Clinical Informatics, 2025)
Background When implemented in both electronic health records (EHRs) and pharmacy management software, CancelRx communicates medication discontinuation in the EHR to pharmacies, which has been demonstrated to reduce medication discrepancies at pharmacies and the risk of medication dispensing after e-prescription discontinuation. Provider workflows for making medication changes and the configuration of CancelRx will affect whether a medication change (e.g., dose adjustment) is communicated to a pharmacy.Objective This study aimed to assess the effect of CancelRx configuration and the EHR tools used in provider workflows for medication changes on notification to health system and external community pharmacies.Methods We conducted a functionality analysis of prescriber workflows for documenting a medication change using “change,” “reorder,” “adjust sig,” “discontinue,” and “taking differently.” In the EHR test environment, we examined three outcomes of interest: communication of discontinuation of the old prescription (or cancellation); generation of a new prescription; and instructions to the patient.Results “Change” was the only single-step function that communicated medication discontinuation to both health system and external community pharmacies with default settings, although “discontinue” followed by a new prescription had the same results. “Reorder” and “adjust sig” functions had different cancellation outcomes for internal and external community pharmacies. “Adjust sig” also had different prescribing outcomes for internal and external pharmacies and “taking differently” did not result in communication of discontinuation or a new prescription at either pharmacy type.Conclusion Several workflows for dose changes did not communicate to external community pharmacies, resulting in different prescriptions at the health system and external community pharmacies. Health systems leaders should consider the implications of local EHR workflows and CancelRx configuration on communication of medication changes to pharmacies as part of CancelRx implementation. Multidisciplinary collaboration is needed to develop more effective strategies for communication of medication dose changes.
Keywords: electronic prescribing; patient safety; electronic health records; community pharmacies